Experience in the management of cornual ectopic pregnancy - Miranda Flores, Alan Francis (2024)
Background: Cornual ectopic pregnancy accounts for 2%-4% of ectopic pregnanciesand is potentially fatal due to uterine rupture and consequent massive hemorrhage,with a mortality rate of up to 2.5%. There is no consensus on the most appropriatemanagement of this pathology. Objective: To describe the experience in themanagement of cornual ectopic pregnancy at the Instituto Nacional MaternoPerinatal, Lima, Peru. Methods: Descriptive and retrospective study of patients witha diagnosis of cornual ectopic pregnancy during the year 2022. Data were obtainedfrom medical records. Statistical analysis was processed in the SPSS 19 program.Results: Out of 9 cases of cornual ectopic pregnancy registered, 7 met the inclusioncriteria. The mean age was 31 years and the mean gestational age 7.3 weeks. Of thecases 71.4% had no risk factors. The majority presented vaginal bleeding associatedwith pelvic pain (71.4%). The average initial value of β-hCG was 8,262.3 mIU/mL. Theaverage size of the tumor was 36.7 mm and 28.6% of the cases presented uterinerupture. 57.1% had surgical treatment consisting of cornual resection, cornuostomyor local injection of methotrexate. Conclusions: Surgery is the most commonly usedtreatment for cornual ectopic pregnancy. In recent years, laparoscopy has becomean important surgical option with certain advantages over laparotomy.